On conspiracy theories - Szymanek, Krzysztof (Folia Philosophica, 2012)
The paper deals with so-called conspiracy theories, that is a kind of explanation of spectacular events, such as catastrophes and terrorist attacks, which is alternative to the mainstream explanations. What conditions should theory meet in order to become recognised as false or unjustified, that is “conspiracy”? Is it possible to draw up a standard test which could differentiate imaginary theories from the legitimate ones? Those questions are addressed in reference to the debate between Brian Kelley and Lee Basham.